2006
DOI: 10.1590/s0074-02762006000600011
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potentiality of Argemone mexicana solvent extracts against some pathogenic bacteria

Abstract: The sensitivity of two Gram positive (Staphylococcus aureus and Bacillus subtilis) and two Gram negative (Escherichia coli and Pseudomonas aeruginosa) pathogenic multi-drug resistant bacteria was tested against the crude extracts (cold aqueous, hot aqueous, and methanol extracts) of leaves and seeds of Argemone mexicana L. (Papaveraceae) by agar well diffusion method. Though all the extracts were found effective, yet the methanol extract showed maximum inhibition against the test microorganisms followed by hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 8 publications
4
38
0
1
Order By: Relevance
“…Negative controls did not show inhibitory action on any of the test organisms, while positive controls significantly inhibited growth of all eight test organisms. The findings match with that of other findings [35][36]. It is often reported that Gram positive bacteria are more sensitive than Gram negative bacteria to plant based organic extracts [37][38][39].…”
Section: Discussion:-supporting
confidence: 92%
“…Negative controls did not show inhibitory action on any of the test organisms, while positive controls significantly inhibited growth of all eight test organisms. The findings match with that of other findings [35][36]. It is often reported that Gram positive bacteria are more sensitive than Gram negative bacteria to plant based organic extracts [37][38][39].…”
Section: Discussion:-supporting
confidence: 92%
“…It occurs as wasteland weed in almost every part of India (Mukherjee and Namhata, 1990; Das and Misra, 1987). In Mexico, the seeds have been used as an antidote to snake poisoning (Bhattacharjee et al, 2006). In India, the smoke of the seeds is used to relieve toothache.…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts have been widely used since ancient times for treating human illnesses. Numerous studies of the antimicrobial activity of different natural products have been reported (Bhattacharjee et al, 2006;Chanda, 2006, 2007;Vaghasiya et al, 2008). Although the medicinal value of pteridophytes has been known to traditional cultures for more than 2000 years, they are used only on a small scale in modern chemotherapy.…”
Section: Antimicrobial Activitymentioning
confidence: 99%